Androstenons fysiologiska roll hos grisar - Jönsson, Ellen (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2010)
It is mainly high levels of androstenone and skatole in adipose tissue that is the reason behind boar-taint, which is an unpleasant odor and taste from the meat of adult male boars. The purpose of this literature study is to provide an overview of current knowledge about the physioloical functioning of androstenone. There are several studies showing androstenone´s function as a pheromone, and that it is an important part of communication and mating behavior between pigs. Androstenone is produced in the testes of the boar and transported via the bloodstream to the salivary glands where it is excreted with the saliva. Sows sense the pheromone, not via the vomeronasal organ as previously considered, but via the olfactory mucosa. The ability to feel the smell of androstenone varies between the sexes and different individuals in which females are more sensitive than males. Genetic correlations between androstenone and skatole may allow one to reduce boar-taint by selective breeding, using individuals with low levels of androstenone. Since androstenone has an important biological function, it may create a risk to breed selectively for low androstenone levels. It is also important to take into account many other factors that may be correlated to androstenone, for example testosterone and growth.